Communication Patterns in Information Dissemination of the Family Hope Program (Program Keluarga Harapan) (Study Case in Sumberdadap Village, Pucanglaban District, Tulungagung Regency) - Fitriana Fatihatul Hasanah; Endah Siswati; Anwar Hakim Darajat (Universitas Islam Balitar, 2023)
Poverty is a persistent and widespread social problem worldwide, including in Indonesia. The Family Hope Program (PKH) is a government initiative in Indonesia aimed at reducing poverty by providing conditional social assistance to eligible poor families identified as beneficiaries of the PKH. Effective dissemination of information is crucial in achieving the program's objectives. This research aims to answer questions regarding the communication patterns, barriers, and ways to overcome them in the dissemination of information for the PKH program. The research method employed is qualitative case study. The researcher collected, reduced, and presented informant responses, supported by observations to interpret the data and draw conclusions. The findings of this study indicate that: 1) The communication pattern in the dissemination of PKH information in Sumberdadap Village involves three direct parties, namely the district coordinator, facilitators, and residents, with the village providing support. 2) Barriers in the dissemination of the PKH program in Sumberdadap Village include technical, semantic, and behavioral barriers. 3) All of these barriers have been overcome through coordination among the district coordinators, facilitators, and PKH beneficiary families.